2019
DOI: 10.17350/hjse19030000157
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Antibacterial and Cytotoxic Properties of Mix Ligand Complex of Zinc 2-Fluorobenzoate with Nicotinamide

Abstract: T he purpose of crystal engineering is to explore new materials with striking properties that can be used in a variety of implementation areas. Metal complexes with an important place in crystal engineering consist of anions or molecules called ligands, which bind to a metal cation and metal atom at the center of symmetry. Metal complexes have been the subject of interest with the diversity of their structures for many years. The structures of metal complexes were determined to be influenced by the biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There is only one study in the literature on the determination of the cytotoxicity of zinc arylcarboxylates with pyridine derivative complexes on normal lymphocyte cells. It was reported that the zinc 2-fluorobenzoic acid nicotinamide complex decreased cell viability with increasing concentration at the 1.17-18.67 mM concentration range (Ozturk and Akbaba, 2019).…”
Section: Mtt Assaymentioning
confidence: 94%
See 2 more Smart Citations
“…There is only one study in the literature on the determination of the cytotoxicity of zinc arylcarboxylates with pyridine derivative complexes on normal lymphocyte cells. It was reported that the zinc 2-fluorobenzoic acid nicotinamide complex decreased cell viability with increasing concentration at the 1.17-18.67 mM concentration range (Ozturk and Akbaba, 2019).…”
Section: Mtt Assaymentioning
confidence: 94%
“…Comparison of cytotoxicity of ZnBrBADENA complex with the starting compounds (Different letters on the columns were significantly different at p<0.05).There is only one study in the literature on the determination of the cytotoxicity of zinc arylcarboxylates with pyridine derivative complexes on normal lymphocyte cells. It was reported that the zinc 2-fluorobenzoic acid nicotinamide complex decreased cell viability with increasing concentration at the 1.17-18.67 mM concentration range(Ozturk and Akbaba, 2019).In addition, it was determined that zinc 2-fluorobenzoate nicotinamide complex caused 13.80-93.58 % cell death in the concentration range of 1250-20000 ppm. Cell death caused by this complex at 10000 ppm is less than the toxicity caused by ZNBrBANA and ZnBrBADENA complexes at 500 ppm(Ozturk and Akbaba, 2019).…”
mentioning
confidence: 98%
See 1 more Smart Citation